Grooved electrodes for high-power-density fuel cells - Lee, ChungHyuk; Kort-Kamp, Wilton J. M.; Yu, Haoran; Cullen, David A.; Patterson, Brian M.; Arman, Tanvir Alam; Komini Babu, Siddharth; Mukundan, Rangachary; Borup, Rod L.; Spendelow, Jacob S. (Nature energy, 2023)
Proton exchange membrane fuel cells (PEMFCs) are leading candidates to decarbonize the transport sector, but widespread deployment will require improvements in lifetime, fuel economy and cost. Here we present the grooved electrode, an alternative electrode structure that enhances PEMFC performance and durability by coupling high ionomer (ion-conducting binder) content for improved H + transport with grooves for rapid O 2 transport. Grooved electrodes provide up to 50% higher performance than state-of-the-art conventional electrodes under standard operating conditions. Fuel cell diagnostics combined with multiphysics modelling demonstrate that grooved electrodes provide facile O 2 transport despite their high ionomer content, enabling improved reaction rate uniformity. Grooved electrodes also provide improved durability, with less performance loss after carbon corrosion compared with baseline electrodes. Machine learning analysis demonstrates the potential to further optimize grooved structures for next-generation PEMFCs with enhanced performance and durability, enabling smaller and cheaper fuel cell stacks with higher fuel efficiency. The way catalysts are arranged and interfaced to form fuel cell electrodes is just as important as the catalysts themselves. Here Lee et al. report an up to 50% increase in performance and superior durability using grooved, rather than conventional flat, electrodes for hydrogen fuel cells.